2018
DOI: 10.1186/s13049-018-0520-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the technical and medical requirements for HEMS avalanche rescue missions through a 15-year retrospective analysis in a HEMS in Switzerland: a necessary step for quality improvement

Abstract: BackgroundAvalanche rescues mostly rely on helicopter emergency medical services (HEMS) and include technical rescue and complex medical situations under difficult conditions. The adequacy of avalanche victim management has been shown to be unexpectedly low, suggesting the need for quality improvement. We analyse the technical rescue and medical competency requirements of HEMS crewmembers for avalanche rescue missions, as well as their clinical exposure. The study aims to identify areas that should be the focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…In this study, the number of male patients, and patients aged 50–64 years with an average age of 48.87 years was significantly higher. Similar demographic features were obtained by other authors analyzing interventions by helicopter medical rescue service crew—Østerås et al (2017), Kottmann et al (2018), Norum and Elsbak (2011) [22,23,24]. Although the studies by Mathiesen et al (2018), McMullan et al (2012), Baker and McKay (2010), and Christensen et al (2017) also showed that male group patients was significantly higher in number, the mean age of patients in their study was higher than identified in this report [25,26,27,28].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, the number of male patients, and patients aged 50–64 years with an average age of 48.87 years was significantly higher. Similar demographic features were obtained by other authors analyzing interventions by helicopter medical rescue service crew—Østerås et al (2017), Kottmann et al (2018), Norum and Elsbak (2011) [22,23,24]. Although the studies by Mathiesen et al (2018), McMullan et al (2012), Baker and McKay (2010), and Christensen et al (2017) also showed that male group patients was significantly higher in number, the mean age of patients in their study was higher than identified in this report [25,26,27,28].…”
Section: Discussionsupporting
confidence: 80%
“…The analysed group of patients consisted mainly of males who made up two-thirds of the entire group, and persons aged 50-64, mean age of the whole group -47.71 years. The results of the authors' own research concerning demographic data of the patients are similar to results obtained by other authors, such as Østerås et al and Kottmann et al [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…Analysis shows that multi-organ injuries and head injuries were the more frequent causes for HEMS missions in rural areas. In Sweden, a study carried out by Kornhall et al concerning HEMS missions in rural areas, showed that the main reasons for the missions were injuries, chest pain and sudden cardiac arrest [23]. In Norway, similar results were obtained by Østerås et al in their study concerning HEMS missions [22].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It is worrying that multiple victim scenarios are so common. In a recent study by Kottmann et al [26], 32% of all rescue operations had more than one casualty. This phenomenon should be addressed in both emergency response and accident prevention.…”
Section: Discussionmentioning
confidence: 99%